The Inverse Problem for Elliptic Equations from Dirichlet to Neumann Map in Multiply Connected Domains. (15th January 2009) - Wen, Guochun; Xu, Zuoliang; Yang, Fengmin
Abstract : The present paper deals with the inverse problem for linear elliptic equations of second order from Dirichlet to Neumann map in multiply connected domains. Firstly the formulation and the complex form of the problem for the equations are given, and then the existence and global uniqueness of solutions for the above problem are proved by the complex analytic method, where we absorb the advantage of the methods in previous works and give some improvement and development.